Studies on Dry Sliding Wear and Solid Particle Erosive Wear Behaviours of Natural Fibre Composite Developed from Water Hyacinth Aquatic Plant for Automotive Application - A. Ajithram; Jappes J. T. Winowlin; Khan M. Adam; N. C. Brintha; Faris Waleed Fekry (Advances in Materials Science and Engineering)
In this research, an attempt is made to investigate the abrasive and erosion wear resistance of aquatic waste plant water hyacinth converted fibre-reinforced polymer composites. From a novel approach, the new fibre extraction machine is designed to extract the hyacinth fibre from the parent plant and reinforce it to the epoxy matrix material to produce a natural fibre composite for frictional applications. The extracted fibre is dried in the open sunlight area for 22 to 35 days to remove moisture and external dust particles. Then, different weight percentages (15, 20, 25, 30, and 35) of composite samples are produced with the help of the hot press compression moulding technique. Improved hyacinth composite tribology properties are tested by utilizing the pin on the disk machine. This setup included various processing parameters like load (10, 20, and 30 N), velocities (1, 2, and 3 m/s), speed (160, 320, and 479 rpm), and constant sliding distance condition, and the erosion setup also influences the essential parameters like impact angle (30, 45, and 60°), erodent velocity (1, 2.5, and 3.3 m/s), and discharge rate (28, 41, and 72 g/m). The factorial techniques are used to identify the important design factors. The final results represent the weight loss, volume loss, and erosion rate of hyacinth fibre composite. By utilizing the SEM (scanning electron microscope), the worn surface morphology of different weight percentages of hyacinth fibre samples are analysed. To upgrade the usage of hyacinth reinforced composites for different industrial applications, wear and erosion studies are conducted with different parameter conditions.